The Effectiveness of Learning Management System (LMS) Use in Higher Education - Herniawati, Ani; Holifah, Laskmi; Syakur, Abd. (CV. Tripe Konsultan, 2025)
This study conducted a systematic review to assess the effectiveness of Learning Management Systems (LMS) in the context of higher education over the past decade. Following PRISMA guidelines and a structured methodological framework, peer-reviewed articles from a range of reputable academic databases were examined to uncover prevailing trends, key challenges, and effective practices in LMS adoption. The analysis demonstrated that LMSs played a significant role in fostering learning motivation, increasing student engagement, and improving the overall quality of the educational experience, particularly in online and blended learning settings. The effectiveness of LMS implementation was influenced by several factors, including the quality of digital instructional materials, the usability of the platform interface, the technological readiness of institutions, and the digital competencies of both educators and learners. Moreover, the review found that LMSs facilitated flexible learning pathways, enabled personalised content delivery, and supported performance tracking through integrated learning analytics. Despite these benefits, notable challenges persisted—most notably disparities in technology access, resistance to pedagogical innovation, and infrastructure deficiencies in underdeveloped, remote, or marginalised areas (commonly referred to as 3T regions: frontier, outermost, and disadvantaged). The study underscored the critical role of LMSs in the ongoing transformation of higher education in the digital era, highlighting the importance of aligning technological tools with pedagogical strategies and institutional policies. Ultimately, the findings provided important guidance for the development of more responsive, inclusive, and sustainable models for LMS integration that address both current demands and future advancements in higher education.